Qizhu Rougan Granules suppress liver fibrosis by inhibiting the expression of the P2Y14 receptor on hepatic stellate cells - Tao, Yujing; Niu, Qun; Yao, Yuanqian; Wang, Kaixin; Dong, Haijian; Zhao, Xin; Zeng, Zijian; Li, Hui (Frontiers in Pharmacology, 2025)
IntroductionLiver fibrosis is a globally prevalent chronic liver disease, often representing the advanced stage of various chronic liver conditions. Despite its widespread occurrence, there is currently no widely accepted or effective treatment for liver fibrosis. However, increasing evidence supports the efficacy of Traditional Chinese Medicine (TCM) in inhibiting the progression of fibrosis. In this study, we explored the effects and potential mechanisms of Qizhu-Ruogan-Granules (QZRG), a formulation from the Affiliated Hospital of the Chengdu University of TCM, on carbon tetrachloride (CCl4)-induced liver fibrosis in mice.MethodsA total of 40 male C57BL/6J mice were randomly divided into five groups (n = 8 per group), with liver fibrosis induced by injecting 10% CCl4 for 15 weeks. From the 7th week onward, QZRG granules were administered orally to the treatment groups at low, medium, and high doses. To assess liver function, serum levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), and alkaline phosphatase (ALP) were measured. Liver morphology and fibrosis were evaluated using hematoxylin-eosin (H&E) and Masson’s trichrome staining, while gene and protein expression levels were analyzed through quantitative reverse transcription polymerase chain reaction (RT-PCR) and western blot techniques.ResultsThe results showed that QZRG granules significantly reduced serum levels of AST, ALT, and ALP in CCl4-treated mice, alleviated liver damage, and reduced collagen accumulation. Furthermore, QZRG granules inhibited the expression of apoptosis-related proteins BAX, Caspase9, Caspase8, and Caspase3, while reducing P2Y14 expression in fibrotic liver tissues. Additionally, QZRG granules suppressed the proliferation of activated hepatic stellate cells.ConclusionOur findings suggest that QZRG granules may exert anti-fibrotic effects by downregulating P2Y14 expression and effectively slowing the progression of liver fibrosis.